Prevention of cardiovascular diseases in Poland – needs and actual status - Zdrojewski, Tomasz (Przewodnik Lekarza/Guide for GPs, 2005)
The author reviews the present epidemiological situation in Poland in the field of cardiovascular diseases, risk factors, and prevention. High prevalence and low control of major risk factors, as well as insuficient knowledge about methods of cvd prevention require urgent complex interventions on population level and in high risk groups. These activities should be integrated with some control and influence on governmental level of the market economy system (food industry) to promote good nutrition and healthy life style. The programs should also follow guidelines and priorities expressed in the “Heart Plan for Europe” and “Healthy Heart” – European Union documents from 2002 and 2004. Complex and compatible national projects were introduced in Poland in 2003 as a part of the National Program for Prevention and Treatment of Cardiovascular Diseases POLKARD (the Polish 400 Cities Project: screening and educational program for citizens of 400 small cities, SPOK: analysis of cardiological standards in primary health care, Polkard-Media: education of general population using TV and radio, SMS: educational multimedia program for children in schools) and last initiatives of the Polish Society of Cardiology (e.g. establishing the Polish Forum for CVD Prevention) should be followed and integrated with longterm programs of the National Health Fund. The present epidemiological situation, dynamic increase of cvd drugs retail, and fast process of “getting older” of the Polish population call for intensive modern prevention as the priority of the national health strategy.